Correlation between serum cryptococcal antigen titre and meningitis in immunocompetent patients. Issue 10 (October 2018) - Gassiep, Ian; Aye, Chaw; Armstrong, Mark; Emeto, Theophilus I.; Heather, Christopher S.; Norton, Robert E.
Abstract : N/A: The aim of this paper was to determine the correlation between serum cryptococcal antigen and a diagnosis of cryptococcal meningitis in the immunocompetent cohort. A retrospective multicentre analysis of immunocompetent patients diagnosed and treated for cryptococcal meningitis between January 2000 and December 2017 was performed. Sixty‐seven of the 143 cases of cryptococcosis occurred in immunocompetent patients. The serum cryptococcal antigen titre was significantly higher in the meningitis group [1 : 256 (IQR: 64‐1024)] compared with that for non‐meningitis patients [1 : 64 (IQR: 8‐256)], P =0.012. The relative risk of meningitis with a serum cryptococcal antigen (CRAG) >1 : 64 was 1.8 (95 % CI: 1.15‐2.82). This study demonstrates a clear correlation between serum cryptococcal antigen titre and meningitis. While the serum titre is not definitive for meningitis, in resource‐limited settings or cases where lumbar puncture may be contraindicated, this evidence may aid diagnosis and subsequent therapeutic decisions.